Manuscript map, Lemon Creek Glacier, Alaska / prepared for the American Geographical Society - Case, James B., 1928–2017 (American Geographical Society of New York, 1957)
Blueline print.; Relief shown by spot heights and contours.; Folded into "IGY Project 4.11 reports. no. 3. Map of the Lemon Creek Glacier, Alaska / J.B. Case," December 1957. Color 1:10,000